ChemInform Abstract: Self‐Assembly and Photocatalytic Properties of Polyoxoniobates: Nb24O72, Nb32O96, and K12Nb96O288 Clusters. Issue 2 (9th January 2013) - Huang, Peng; Qin, Chao; Su, Zhong‐Min; Xing, Yan; Wang, Xin‐Long; Shao, Kui‐Zhan; Lan, Ya‐Qian; Wang, En‐Bo
Abstract The new compounds (III), (IV), and (V) with molecular triangle, molecular square, and cuboctahedral molecular cage geometries, respectively, are characterized by single crystal XRD and electrospray ionization mass spectrometry.